Can autonomy support have an effect on type 2 diabetes glycemic control? Results of a cluster randomized controlled trial. Issue 1 (16th April 2020) - Yun, Qingping; Ji, Ying; Liu, Shenglan; Shen, Yang; Jiang, Xuewen; Fan, Xinyi; Liu, Jingnan; Chang, Chun
Abstract : Objectives: To assess whether social support or autonomy support intervention for patients with type 2 diabetes can achieve glycemic control at the end of intervention, and to test whether the glycemic control effect can be maintained for a long time. Research design and methods: In this cluster randomized controlled trial, 18 community healthcare stations (CHSs) were randomized to the following: (1) usual care group (UCG) offering regular public health management services, (2) social support group (SSG) providing 3-month social support intervention based on problem solving principles, and (3) autonomy support group (ASG) offering 3-month autonomy support intervention based on self-determination theory. A total of 364 patients registered in the CHSs were enrolled into either of the three groups. The primary outcome was hemoglobin A1c (HbA1c), and secondary outcomes were diabetes self-management (DSM) behaviors. Assessment was conducted at baseline and at 3 and 6 months. Results: Patients in ASG achieved better HbA1c reduction at the end of intervention (0.53% or 7.23 mmol/mol, p < 0.001) than those in the UCG and successfully maintained it up to 6 months (0.42% or 5.41 mmol/mol, p < 0.001). However, patients in SSG did not experience significant change in HbA1c at 3 or 6 months when compared with patients in UCG. Besides, patients in both the SSG (0.12, p < 0.05) and ASG (0.22, p < 0.001) experienced improvement in exercise at 3 months. Patients in ASG sustained improvement in exercise up to 6 months (0.21, p<0.001), but those in the SSG did not. Conclusions: Autonomy support for patients with type 2 diabetes could help achieve glycemic control at the end of intervention and successfully maintain it up to 6 months. These findings indicate that autonomy support has positive long-term effects on DSM behaviors and glycemic control and can be recommended in future diabetes intervention programs. Trial registration number: ChiCTR1900024354.